Mobile and high-spectral-resolution Fabry-Pérot interferometer spectrographs for atmospheric remote sensing - Kuhn, Jonas; Bobrowski, Nicole; Wagner, Thomas; Platt, Ulrich (Atmospheric measurement techniques, 2021)
Abstract. Grating spectrographs (GS) are presently widely in use for atmospheric trace gas remote sensing in the ultraviolet (UV) and visible spectral range (e.g. differential optical absorption spectroscopy, DOAS). For typical DOAS applications, GSs have a spectral resolution of about 0.5 nm, corresponding to a resolving power R (ratio of operating wavelength to spectral resolution) of approximately 1000. This is sufficient to quantify the vibro-electronic spectral structure of the absorption of many trace gases with good accuracy and further allows for mobile (i.e. compact and stable) instrumentation. However, a much higher resolving power (R≈105, i.e. a spectral resolution of about the width of an individual rotational absorption line) would facilitate the measurement of further trace gases (e.g. OH radicals), significantly reduce cross interferences due to other absorption and scattering processes, and provide enhanced sensitivity. Despite these major advantages, only very few atmospheric studies with high-resolution GSs are reported, mostly because increasing the resolving power of a GS leads to largely reduced light throughput and mobility. However, for many environmental studies, light throughput and mobility of measurement equipment are central limiting factors, for instance when absorption spectroscopy is applied to quantify reactive trace gases in remote areas (e.g. volcanoes) or from airborne or space-borne platforms. For more than a century, Fabry-Pérot interferometers (FPIs) have been successfully used for high-resolution spectroscopy in many scientific fields where they are known for their superior light throughput. However, except for a few studies, FPIs have hardly received any attention in atmospheric trace gas remote sensing, despite their advantages. We propose different high-resolution FPI spectrograph implementations and compare their light throughput and mobility to GSs with the same resolving power. We find that nowadays mobile high-resolution FPI spectrographs can have a more than 2 orders of magnitude higher light throughput than their immobile high-resolution GS counterparts. Compared with moderate-resolution GSs (as routinely used for DOAS), an FPI spectrograph reaches a 250 times higher spectral resolution while the signal-to-noise ratio (SNR) is reduced by only a factor of 10. Using a first compact prototype of a high-resolution FPI spectrograph (R≈148 000, <8 L, <5 kg), we demonstrate that these expectations are realistic. Using mobile and high-resolution FPI spectrographs could have a large impact on atmospheric near-UV to near-infrared (NIR) remote sensing. Applications include the enhancement of the sensitivity and selectivity of absorption measurements of many atmospheric trace gases and their isotopologues, the direct quantification of OH radicals in the troposphere, high-resolution O2 measurements for radiative transfer and aerosol studies, and solar-induced chlorophyll fluorescence quantification using Fraunhofer lines.